The Role of Profitability in Moderating the Relationship between Environmental, Social, Governance (ESG) and Company Value - Amalia, Hilda; Bertuah, Eka (LifeSciFi, 2025)
Growing awareness of Environmental, Social, and Governance (ESG) issues has made sustainability a key factor in corporate performance, influencing both stakeholder trust and financial outcomes. This study aims to analyze the influence of Environmental, Social, and Governance (ESG), profitability, and the interaction of both on the company’s value in issuers included in the LQ45 index on the Indonesia Stock Exchange (IDX) for the 2022 until 2024 period. The research sample comprises companies that are members of the LQ45 index, selected through a purposive sampling method. Data analysis was carried out using multiple linear regression. The results indicate that ESG has a significant impact on a company’s value, and the inclusion of profitability enhances the model’s ability to explain variations in company values. The value of the determination coefficient in all three models was in the range of 94%, indicating that the model has a very high ability to explain variations in the company’s value. In contrast, factors outside the model influence the remaining variation. The F-test in all three equations indicates that all independent variables collectively have a significant impact on the company’s value. However, this study has limitations because the sample consists only of LQ45 companies, so the results may not fully reflect the characteristics of all types of industries, given that ESG implications can differ in each sector.